Heating Performance Study on a Passive Solar Heater - Naz, M.Y. (EDP Sciences, 2017)
A passive thermosyphon heating system was designed, fabricated and tested for its thermal performance in semi-arid and four-season climate of Pakistan. The heating system design was based on a two-stage storage and natural thermosyphon circulation of the water. The objective of the study was to enhance the heating performance of the thermosyphon systems by using a semicircular steel pot collector, water carrying copper coil cover, two step water storage, and side mirror reflectors. The experiments were conducted during April to July 2014 when ambient temperature was reported to vary between 32°C and 44°C. In continuous flow mode operation, the hot water temperature remained between 46°C and 78°C. Since water temperature in the range of 45°C to 50°C is considered suitable for the domestic use, the presented design can easily reach the temperatures even higher than those acceptable for the domestic use. © The authors, published by EDP Sciences, 2017.